Influence of using simulated or real patients on undergraduate medical students acquiring competencies in medical conversations in surgery: A prospective, controlled study - Britz, Vanessa; Koch, Yannic; Schreckenbach, Teresa; Stefanescu, Maria Christina; Zinßer, Uwe; Sterz, Jasmina; Ruesseler, Miriam (Frontiers in Surgery, 2022)
Background Communication with patients and their relatives as well as with colleagues and students is an essential part of every physician's daily work. An established method for teaching communication skills is using simulated patients (SPs). However, teaching with SPs is often subjectively perceived by medical students as less instructive than teaching with real patients (RPs). Studies that analyze the influence of SPs compared to RPs for acquiring competencies are lacking. The aim of the present study was therefore to investigate the impact of SPs on long-term learning success for communication skills compared to RPs. Material and Methods Study participants were undergraduate third-year medical students who attended a communication unit and were randomized into three groups. The first group trained the role-play part with a SP (SP-group). The second group trained with a SP but thought that the patient was a RP because the students and the tutors were told that they were a RP by the principal investigator (incognito patient group [IP-group]). The third group and their tutors trained with a RP and were told that the patient was a RP (real patient group [RP-group]). Five to 12 weeks after completing the training, the study participants completed a curricular summative objective standardized clinical examination. Results There were 146 students who participated in the study. There were no significant differences between the three study groups at the informed consent stations and for those conducting anamnesis interviews. Conclusion Communication skills training with SPs appears to be equivalent to training with RPs in terms of competency development in communication-based assessments in surgery. Therefore, SPs should be used in these curricula, especially at an early stage, to enable the students to practice adequate communication skills.